2012
DOI: 10.1371/journal.pone.0035758
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Epithelial Cells from the Human Placenta Potently Suppress a Mouse Model of Multiple Sclerosis

Abstract: Human amniotic epithelial cells (hAEC) have stem cell-like features and immunomodulatory properties. Here we show that hAEC significantly suppressed splenocyte proliferation in vitro and potently attenuated a mouse model of multiple sclerosis (MS). Central nervous system (CNS) CD3+ T cell and F4/80+ monocyte/macrophage infiltration and demyelination were significantly reduced with hAEC treatment. Besides the known secretion of prostaglandin E2 (PGE2), we report the novel finding that hAEC utilize transforming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 46 publications
2
79
2
Order By: Relevance
“…They also found that HAECs reduced proliferation of T cells and decreased their secretion of proinflammatory cytokines 32. More recently Liu et al reported that intravenously administered HAECs reduced CD3+ T cell and F4/80(+) monocyte/macrophage infiltration and demyelination within the CNS of an EAE mouse 70. HAECs immunosuppression was mediated by PGE2 and TGF-β, as it was demonstrated by the neutralization of TGF-β or PGE2 in splenocyte proliferation assays.…”
Section: Potential Use Of Am-derived Stem Cells To Treat Inflammatorymentioning
confidence: 87%
“…They also found that HAECs reduced proliferation of T cells and decreased their secretion of proinflammatory cytokines 32. More recently Liu et al reported that intravenously administered HAECs reduced CD3+ T cell and F4/80(+) monocyte/macrophage infiltration and demyelination within the CNS of an EAE mouse 70. HAECs immunosuppression was mediated by PGE2 and TGF-β, as it was demonstrated by the neutralization of TGF-β or PGE2 in splenocyte proliferation assays.…”
Section: Potential Use Of Am-derived Stem Cells To Treat Inflammatorymentioning
confidence: 87%
“…This could be due to the previously described epithelial-to-mesenchymal cell transition that amniotic epithelial cells undergo after various passages in culture (37). Both in vitro and in vivo studies have demonstrated that cells from either the epithelial or mesenchymal layers exert immunomodulatory properties and ameliorate disease with inflammatory bases, including lung and liver fibrosis and EAE (15,19,(38)(39)(40)(41). Interestingly, an important percentage of the HAMCs used in our study expressed CD106 (vascular cell adhesion molecule 1), which identifies a subpopulation of mesenchymal stem cells with unique immunoregulatory properties in various tissues, especially in the placenta (42).…”
Section: Discussionmentioning
confidence: 99%
“…Mixed lymphocyte reaction (MLR) assays revealed that hAECs inhibited 66%-93% of lymphocyte activation in a dose-dependent manner [23]. In addition to these soluble forms of cell surface molecules, hAECs secrete other immunosuppressive factors, including prostaglandin E2 (PGE2), insulin-like growth factor II, plateletderived growth factor, transforming growth factor-b2 (TGF-b2), and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) [6,17,[24][25][26][27][28]. hAECs also release anti-inflammatory cytokines and proteins, including interleukin (IL)-1 receptor antagonist protein; tissue inhibitors of metalloproteinase1-1, -2, -3, -4; and IL-10 [29,30].…”
Section: Immunomodulatory Effectmentioning
confidence: 99%